Kuala Terengganu Water Taxi Operators Affective Commitment: An Exploratory Qualitative Case Study - Bahyah, Abdul Halim (2013)
At present, the usage and attractiveness of the Water Taxi is declining significantly. Despite the declining trend, these Water Taxi Operators will drive their boats every day from dawn till dusk without fail. The case study is aimed to investigate the influencing factors that contribute to affective commitment amongst the Water Taxi Operators in Kuala Terengganu according to The Three Component Model of Commitment developed by Allen, N.J. & Meyer, J.P. (1990). It is well known that the Water Taxi in Kuala Terengganu has been alive for the past 50 years. Thus, the researcher is determined to gather empirical qualitative findings for this exploratory case study. Data were obtained from interview sessions with the Water Taxi Operators and observations were carried out at their work setting. It is found that the influencing factors for these Water Taxi Operators to stay committed and passionate to the job are for economic reasons, the desire to preserve the Terengganu heritage, the love and passion towards the sea and boats, the opportunity for socialization and to stay mentally and physically healthy and fit.